Memorandum of understanding as an employer branding tool for Walton Hi-Tech Industries PLC - Md. Arifin Doha, Akhond (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.